Heavy metals – a silent threat to health - Kosek-Hoehne, Karolina; Panocha, Błażej; Śliwa, Anna (Journal of Education, Health and Sport, 2017)
Progressing environmental pollution is a threat for modern human – especially when it comes to toxic influence of heavy metals on human body. Increasing the awareness about the problem of negative influence of those metals is an important aspect of preventive treatment. This thesis describes the negative influence of heavy metals on human body. Most often, these metals enter the body by ingestion but also by inhalation or through the skin. Accumulation of toxins in the body is limited by biological barriers. However, excessive amounts of such toxins are still a threat to human health. They can cause acute intoxication and chronic toxicity which might result in digestive and neural problems and even internal organs damage. This thesis describes chosen heavy metals which are toxic for human body, characteristic symptoms of chosen metal intoxication types and prevention methods. The examples are: the influence of lead on central nervous system, on anomalies in fetal nervous system development and the influence of tobacco smoke toxins on fetal development during pregnancy. Environmental pollution makes it impossible to produce goods and food from products completely free from heavy metals contamination. That is why we should focus on reducing the amount of heavy metals to the minimum when it comes to the world around us.